Response of bacterial communities and plant-mediated soil processes to nitrogen deposition and precipitation in a desert steppe - Wang, Zhen; Na, Risu; Koziol, Liz; Schellenberg, Michael P.; Li, Xiliang; Ta, Na; Jin, Ke; Wang, Hai (Plant and soil, 2020)
Background and aims Changes in nitrogen (N) and precipitation levels can substantially alter soil properties and plant growth, thereby altering soil microbial diversity and functionality. Method We used manipulated precipitation treatments (50% reduction, control, and plus 50%) and tested two N fertilization levels (control and plus 35 kg N ha −1 yr −1 ) from a 4-year field experiment to evaluate the effects on soil bacterial diversity, community composition, and N-cycle gene abundance. Results N additions significantly increased ammonia-oxidizing bacterial abundance (via AOB- amoA ) but decreased denitrification genes (i.e., nirS and nosZ ). Decreased precipitation significantly decreased the abundance of N-cycle genes (AOB- amoA , nirS , and nosZ ), while increased precipitation conversely increased the abundance of these same genes. Decreased precipitation led to differences in the microbial community composition that favored drought resistance, indicating that plant-associated microbiomes may be able to modulate plant growth fitness in the context of extreme environmental conditions. N additions substantially altered soil bacterial communities, increasing the relative abundance of certain bacteria and of nitrification-related genes in a manner that depended on precipitation fluctuations. Conclusions Differences in the bacterial community composition and N-cycle genes determined the functional response of a grassland ecosystem to decreased precipitation conditions, and therefore could affect the influence of N deposition on plant growth as well as the physical and chemical properties of the soil.